1997
DOI: 10.1111/j.1432-1033.1997.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Repression of Translation by Wortmannin and Rapamycin

Abstract: The role of phosphatidylinositol 3-kinase and FKSO6-binding protein . rapamycin-associated protein (FRAP) in translational control has been examined by treating RD-rhabdomyosarcoma cells with wortmannin and rapamycin and studying the effects on cell-growth, translation initiation, and protein synthesis. Whereas wortmannin and rapamycin exhibit subtle effects on global translation, examination of individual mRNAs in sucrose gradients and of individual proteins in two-dimensional polyacrylamide gels reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…For example, rapamycin and LY294002 inhibited nitric oxide production in Raw 264.7 cells, whereas wortmannin is ineffective (61). Likewise, studies in several different cell types have revealed that wortmannin and rapamycin exhibit distinct effects on the translation of individual mRNAs (62). Thus, it appears that there are multiple pathways leading to mTOR activation, which are utilized in different cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rapamycin and LY294002 inhibited nitric oxide production in Raw 264.7 cells, whereas wortmannin is ineffective (61). Likewise, studies in several different cell types have revealed that wortmannin and rapamycin exhibit distinct effects on the translation of individual mRNAs (62). Thus, it appears that there are multiple pathways leading to mTOR activation, which are utilized in different cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…These results can be explained by the presence of an oligopyrimidine tract in the 5Ј-untranslated region of the cyclin D1 mRNA. However, other mRNA determinants could be involved, since about 30% of newly synthesized proteins are inhibited by rapamycin (19,44). Rapamycin's target is the immunophilin FK506-binding protein, which binds to the kinase FRAP/ mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…In serum-starved cells as well as in cells treated with the macrolide antibiotic rapamycin, S6 becomes rapidly dephosphorylated, and 5ЈTOP mRNAs are no longer translated. Analysis of rapamycin-treated cells reveals that the steady-state distribution of these mRNAs shifts from polyribosomes to smaller ribonucleoprotein particles of unknown composition (Jefferies et al, 1997;Pedersen et al, 1997). The existence of 5ЈTOP sequences in mice as well as Xenopus suggests that this mechanism is conserved among metazoans (Meyuhas et al, 1996).…”
Section: Introductionmentioning
confidence: 99%